Implementation of Green Human Resources Management (GHRM) at PT. Pertamina Patra Niaga Fuel Terminal Samarinda to Support Company Sustainability - Isnawati, Isnawati; Tuti Wediawati; Annisa Wahyuni Arsyad; Fareis Althalets (Journal of Management and Bussines (JOMB), 2025)
This study aims to analyze the implementation of Green Human Resource Management (GHRM) at PT. Pertamina Patra Niaga Fuel Terminal Samarinda in supporting the company's aspirations. The research method used a descriptive qualitative approach, collecting data through interviews, observation, and documentation. The research also involved informants from the Community Development Officer (CDO) and HSSE Supervisors. The results indicate that the implementation of GHRM has been integrated into HR management practices through environmental training, energy efficiency, digitalization, and waste management, and is supported by a green organizational culture such as the Bank Ramli program, reforestation, and the Biodiversity (Kehati) program. The conclusion of this study is that GHRM has a positive impact on environmental compliance, increasing employee awareness, and achieving desired goals. Although its implementation still requires ongoing evaluation and monitoring to remain effective and relevant in the future.   Keywords: Green Human Resource Management, Sustainability, Energy